PSYCHOLOGICAL BASIS OF FORMING A SPORTS COACH'S PROFESSIONAL IMAGE - Shkarlatiuk, Kateryna; Koshyrets, Viktor; Hubina, Alla (My University, 2024)
Purpose. Grounding psychological conditions and ways of forming a professional image based on the disclosure of the structure and image characteristics of a sports coach. Methods. The following theoretical and empirical methods were used: analysis, synthesis, generalization; a complex of psychodiagnostic methods which allowed to reveal the content and functional parameters of the professional image. For statistical data processing, the Spearman’s coefficient was calculated. Results. The professional image of a sports coach as a factor of the effectiveness of professional activity is an image of a personality determined by the requirements of the profession and consisting of a relatively constant core (self-concept, social role, values of professional activity and interaction, professionally significant personal qualities) and an external component (culture of communication, choice of a certain model of behavior). Conclusions. A positive professional image depends on the inner «Self» of a coach: a system of values, beliefs, interests, desires. Such a person has his own dignity, self-respect, is able to be responsible for himself and his future, high professional self-esteem, flexibility in finding creative alternatives. Individual and psychological characteristics of the coach’s personality, which are determinants of the formation of an effective professional image and their manifestation when working with teams, can be used in the process of forming the professional image of a sports coach. The evaluative and productive aspect of the significance of professional activity is based on the synthesis of ideas about the physical and spiritual state of the professional, the influence of colleagues, appearance, professional competencies necessary in the course of performing production tasks.

Мета. на основі розкриття структури професійного іміджу фахівця, дослідження іміджевих характеристик спортивного тренера обґрунтувати психологічні умови та шляхи формування професійного іміджу. Методи. Для досягнення мети було застосовано такі науково-теоретичні методи : аналіз, синтез, узагальнення, комплекс психодіагностичних методик, що дозволили розкрити змістові та функціональні параметри професійного іміджу. Для статистичної обробки даних розраховано коефіцієнт Спірмена. Результати. Професійний імідж тренера як фактор ефективності професійної діяльності, є образом особистості, що визначається вимогами професії і складається з відносно постійного стрижня (Я-концепція, соціальна роль, цінності професійної діяльності та взаємодії, професійно значимі особистісні якості) та зовнішньої складової (культура спілкування, вибір певної моделі поведінки). Висновки. Позитивний професійний імідж залежить від внутрішньої сутності людини: системи цінностей, переконань, інтересів, бажань. Така людина має власну гідність, самоповагу, здатна нести відповідальність за себе та своє майбутнє, високу професійну самооцінку, гнучкість у пошуку творчих альтернатив. Індивідуально-психологічні особливості особистості тренера, які є детермінантами формування дієвого професійного іміджу та їх прояв при роботі з командами, можуть бути використані в процесі формування професійного іміджу спортивного тренера. Оціночно-результативний аспект професійної діяльності ґрунтується на синтезі уявлень про фізичний та духовний стан фахівця, вплив з боку колег, зовнішній вигляд, професійні компетенції, необхідні в ході виконання виробничих завдань.
Keywords: personal qualities; professional image; sports coach; professional value orientations; communicative competence; image formation